Measurement of Amniotic Fluid Interleukin-6 Using Commercial Kits - Tsunenobu Tamura; William W. Andrews; Kelley E. Johnston; G. Philamon Hemstreet; Robert L. Goldenberg (Hindawi Limited, 1997)
Objective: The association between increased amniotic fluid interleukin-6 (IL-6) concentrations and preterm labor has received increasing attention. Several research groups have evaluated this association using commercial IL-6 kits, which principally use the sandwich-enzyme-immunoassay method, and were originally created to measure IL-6 in plasma, serum, or culture media. We evaluated commercial kits for the determination of IL-6 in amniotic fluid.